Developing growth mindsets in engineering students: a systematic literature review of interventions. (4th July 2021) - Campbell, Anita L.; Direito, Inês; Mokhithi, Mashudu
ABSTRACT: Dropout from engineering studies has been linked to 'fixed mindset' beliefs of intelligence as fixed-at-birth that make students more likely to disengage when facing new challenges. In contrast, 'growth mindset' beliefs that intelligence can be improved with effort make students more likely to persist when confronting difficulties. This systematic literature review of engineering, education and psychology databases explores the effectiveness of different interventions in developing growth mindset in engineering students, what measures have been used in assessing the effectiveness of these interventions and who has benefited from these interventions, in terms of gender and year of study. We compare interventions by geographical location, intervention type, methodology for assessing mindsets, other topics studied, and effectiveness. The results show a variation in effectiveness among the fifteen included studies. The findings will be useful for educators who want to encourage growth mindset and thereby support the academic success of their students.